Change Leadership Practices at the University of Khartoum, Sudan - Onia, Saifaldin Idris; Gedifew, Matebe Tafere; Sahile, Amare (Technium Social Sciences Journal, 2021)
This study aimed to examine change leadership practices at the University of Khartoum with a major purpose of enhancing the importance and understanding of change leadership practices at the University of Khartoum. This study tried to capture staff members’ perception of the creating a climate for change, engaging and enabling the whole organization and implementing and sustaining change. In doing so, a survey research design was employed. Data were collected using questionnaire from university's staff members. The result shows high level of change leadership practices in the University of Khartoum with its different dimensions. Consequently, creating a climate for change has practiced in the University of Khartoum. The University of Khartoum has engaged and enabled the whole organization in the change process. The findings indicate that the University of Khartoum has implemented and sustained change process. Besides, no statistically significant difference between the male and female groups in the extent of change leadership practices. Therefore, it was reflected that the university leaders should make a strong case for the necessity of the change prior to implementation. Overall, the vision, strategies and objectives of the University of Khartoum should involve the importance of change. In addition, extra efforts should be made to maintain change leadership culture in the University of Khartoum.